Penerapan Model Porpe Berbantuan Media Animasi Plotagon dalam Pembelajaran Menulis Teks Cerita Fantasi Berorientasi pada Berpikir Kreatif Peserta Didik Kelas VII SMPN 35 Bandung - resita, Ayu resita; Dheni Harmaen; Rendy Triandy (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This study is based on the selection of models and media that are less creative and innovative in learning to write fantasy story texts so that students feel bored and have difficulty in writing activities. This study aims to test the effectiveness of learning to write fantasy story texts with the porpe model assisted by plotagon animation media on students of class VII SMPN 35 Bandung. This study uses a quantitative method of the quasi-experimental type and a true experimental pretest-posttest control group design, and the research subjects consist of 2 classes.  The results of the study showed 1) the author was able to plan and implement learning to write fantasy story texts, as evidenced by the scores obtained of 3.63 and 3.55 with a very good category, 2) the ability of students after receiving treatment had reached the Learning Objective Achievement Criteria (KKTP) with a total average obtained of 89.02. 3) the difference in student abilities before and after receiving treatment using the plotagon animation media-assisted porpe model experienced a significant increase as evidenced by the wilcoxon test results showing an Asymp. Sig. (2-tailed) <0.05. 4) the plotagon animation media-assisted porpe model is effective for use in learning to write fantasy story texts as evidenced by the results of the maan whitney test showing an Asymp. Sig. (2-tailed) value, namely 0.00, <0.05. which means that the plotagon animation media-assisted porpe model is more effective to use compared to the control class.